2012
DOI: 10.1523/jneurosci.0889-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Silencing GSK-3 Isoforms Reduces Plaques and Tangles in Mouse Models of Alzheimer's Disease

Abstract: Glycogen synthase kinase-3 (GSK-3) is linked to the pathogenesis of Alzheimer’s disease (AD) senile plaques (SPs) and neurofibrillary tangles (NFTs), but the specific contributions of each of the GSK-3 α and β isoforms to mechanisms of AD have not been clarified. In this study, we sought to elucidate the role of each GSK-3α and β using novel viral and genetic approaches. First, we developed recombinant adeno-associated virus 2/1 short hairpin RNA constructs which specifically reduced expression and activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
86
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 46 publications
5
86
0
Order By: Relevance
“…It is important to note that L803-mts had a preventative effect, because treatment was begun prior the appearance of A␤ pathology. Our results corroborate previous studies that showed that inhibition in GSK-3 activity reduced A␤ production and/or A␤ pathology (14,16,17). The one study that showed that knock-out of GSK-3␣ or GSK-3␤ in the mouse brain did not affect APP metabolism or A␤ levels (15) was performed using an in vivo model that lacked A␤ pathology, and the role of GSK-3 might have been masked under these conditions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is important to note that L803-mts had a preventative effect, because treatment was begun prior the appearance of A␤ pathology. Our results corroborate previous studies that showed that inhibition in GSK-3 activity reduced A␤ production and/or A␤ pathology (14,16,17). The one study that showed that knock-out of GSK-3␣ or GSK-3␤ in the mouse brain did not affect APP metabolism or A␤ levels (15) was performed using an in vivo model that lacked A␤ pathology, and the role of GSK-3 might have been masked under these conditions.…”
Section: Discussionsupporting
confidence: 91%
“…80). It should be noted, however, that GSK-3␣ was previously implicated in A␤ production (14) and A␤ plaque formation (17). Thus, it is possible that GSK-3 isozymes influence A␤ pathology by similar and by distinct pathways (14,16,81,82).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our screen data suggested that not only is GSK3␤ a good candidate target but that GSK3␣ is also a strong candidate tau kinase as GSK3␣ exhibited the greater magnitude of phosphorylation at all the AD-associated epitopes tested. Moreover, a recent study exploring the specific contributions of each of the GSK3␣ and -␤ isoforms in AD disease progression by using selective viral and gene silencing techniques in transgenic mouse models of AD has been described (21). Their data indicate that GSK3␣ contributes to ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication showed that the selective silencing of either GSK3a or GSK3b leads to different consequences in mouse models of Alzheimer's disease [37]. GSK3a-, but not GSK3b-, silenced amyloid precursor protein transgenic mice exhibited reduced levels of amyloid b formation in the adult hippocampus, which indicates the characteristic roles of GSK3a and GSK3b in neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%